Políticas de segurança pública no Brasil: uma análise das leis aprovadas entre 1995 e 2022 - Lino, Lillian Lages (Universidade Federal de São Carlos, 2025)
Since the redemocratization, public security policies in Brazil have undergone successive legal and institutional reforms, driven by recurring crises and social pressure for more effective responses to crime and violence. These transformations reflect not only conjunctural reactions but also ideological disputes regarding the roles assigned to the State, punishment, and protection in the implementation of public policies. Based on this context, the study recognizes that the post-1988 period was marked by distinct political-ideological orientations, delimiting the research timeframe between 1995 and 2022. This interval encompasses a phase of relative democratic stability and three blocks of institutional change: the liberal pattern during the governments of Fernando Henrique Cardoso, the neo-developmentalist pattern under Lula and Dilma Rousseff’s administrations, and the pattern of democratic regression observed during the governments of Michel Temer and Jair Bolsonaro. In this light, this research proposes to investigate, from the tension between the paradigms of punishment and protection, how and in which direction public security policies were modified throughout this period. The analysis combines David Garland’s (2001) typology of state models of crime control, its application to the Brazilian context by Azevedo and Cifali (2015), and the framework of gradual institutional change developed by Streeck and Thelen (2005) and systematized by Mahoney and Thelen (2010). This combined approach allows not only for identifying and classifying normative changes – from penal toughening to the approval of prevention policies and rights guarantees – but also for understanding how incremental adjustments gradually shift the axis of public policies between punitive and protective rationalities. The research integrates two complementary movements – one theoretical-historical and the other empirical – using a database of 60 approved laws, which were initially analyzed quantitatively and later subjected to qualitative content analysis, focusing on 9 laws identified as substantive policies in the field. The thesis of misalignment emerges, according to which the relationship between the ideological profile of governments and the type of policy adopted is not linear, highlighting the complexity of institutional arrangements and normative disputes shaping the public security field. Nonetheless, the study points out that public security policies primarily change through layering. The analysis seeks to reveal the ideological vectors underlying these transformations and, by demonstrating how specific normative decisions accumulate effects over time, contributes to Political Science by offering a deep understanding of the reconfiguration of the State’s role in addressing crime and insecurity management in contemporary Brazil.
Public security policies in Brazil: a legislative analysis of laws enacted between 1995 and 2022
Keywords: Segurança pública; Mudanças em políticas públicas; Leis ordinárias; Punitivismo; Políticas públicas; CIENCIAS HUMANAS::CIENCIA POLITICA; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS; CIENCIAS HUMANAS; 16. Paz, Justiça e Instituições Eficazes; 10. Redução das Desigualdades; 17. Parcerias e Meios de Implementação